2017
DOI: 10.1186/s12711-017-0334-1
|View full text |Cite
|
Sign up to set email alerts
|

Genetic assessment of residual feed intake as a feed efficiency trait in the Pacific white shrimp Litopenaeus vannamei

Abstract: BackgroundResidual feed intake (RFI) was investigated as a measure of feed efficiency in a breeding population of Litopenaeus vannamei. Shrimp from 34 families were housed individually and feed efficiency and growth traits were recorded during two successive growth periods. The objectives of this study were (1) to estimate the heritability of RFI and related traits, including feed efficiency ratio (FER), average daily gain (ADG) and daily feed intake (DFI), (2) to determine the relationships between RFI and ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Daily feed intake (DFI) and feed efficiency ratio (FER) were estimated as the measures of feed efficiency. The mean unweighted FER was higher (0.66) in Pacific white shrimp compared with Chinese white shrimp (0.24) in the pre‐harvest stage (Dai, Luan, Lu, Luo, Meng, et al, 2017). A wide range of reproductive traits were recorded across studies at the mature stage.…”
Section: Resultsmentioning
confidence: 96%
“…Daily feed intake (DFI) and feed efficiency ratio (FER) were estimated as the measures of feed efficiency. The mean unweighted FER was higher (0.66) in Pacific white shrimp compared with Chinese white shrimp (0.24) in the pre‐harvest stage (Dai, Luan, Lu, Luo, Meng, et al, 2017). A wide range of reproductive traits were recorded across studies at the mature stage.…”
Section: Resultsmentioning
confidence: 96%
“…RFI is defined as the difference between the observed feed intake and the expected feed intake for maintenance and growth of an individual (Koch et al, 1963). Research has shown that genetic selection for RFI could improve feed efficiency and reduce feed intake without affecting growth performance (Dai et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Genetic parameters estimates for FE traits are relatively rare in aquaculture species, but have been extensively assessed in livestock species with significant heritabilites detected, ranging from 0.13 up to 0.84 ( de Verdal et al, 2011 ; Case et al, 2012 ; Freetly et al, 2020 ; Tortereau et al, 2020 ; Marchesi et al, 2021 ). The studies on aquaculture species have also detected moderate to high heritabilities (0.57–0.71) for average daily gain (ADG), daily feed intake (DFI), feed efficiency ratio (FER) and RFI in a breeding Pacific white shrimp ( Litopenaeus vannamei ) population ( Dai et al, 2017 ). Furthermore, Kause et al (2006) found significant heritabilities for growth in rainbow trout ( Oncorhynchus mykiss ), but not for FI, whereas Dvergedal et al (2019) found significant heritabilities ranging from 0.18 to 0.45 for several feed efficiency traits in Atlantic salmon, such as weight gain, residual weight gain, and stable isotope profile in food.…”
Section: Discussionmentioning
confidence: 99%
“…high heritabilities (0.57-0.71) for average daily gain (ADG), daily feed intake (DFI), feed efficiency ratio (FER) and RFI in a breeding Pacific white shrimp (Litopenaeus vannamei) population (Dai et al, 2017). Furthermore, Kause et al (2006) found significant heritabilities for growth in rainbow trout (Oncorhynchus mykiss), but not for FI, whereas Dvergedal et al (2019) found significant heritabilities ranging from 0.18 to 0.45 for several feed efficiency traits in Atlantic salmon, such as weight gain, residual weight gain, and stable isotope profile in food.…”
Section: Heritability and Genetic Correlationsmentioning
confidence: 99%